Mahakal Blessed My Crop: Community Dynamics and Religious Beliefs Influence Efficacy of a Wildlife Compensation Program - Kshettry, Aritra; Bhave, Nupur; Das, Priyanka; Athreya, Vidya (Frontiers in Conservation Science, 2021)
Conservation conflicts or human-wildlife conflicts present one of the foremost challenges to wildlife conservation globally. The challenges of reconciling human safety and food security with the conservation of large-bodied wildlife are further compounded in the developing nations with a high spatial overlap of wildlife with people. Therefore, conservation models are required to offset losses faced by affected communities while at the same time ensuring the long-term conservation of wildlife species in shared spaces. Ex-gratia payment is one such widely used conflict mitigation instrument that aims to reduce losses and increase tolerance toward damage-causing wildlife species. However, the efficacy of such programs is rarely investigated and the complex interplay of local beliefs, traditions, and community dynamics are rarely incorporated in the compensation programs. This paper aimed to study an ex-gratia payment program for crop losses in India using ecological, economic, and social lenses. In this study, we used 119 interview surveys across 30 villages. Linear models and thematic analysis were used to understand the sources of crop losses, the propensity to claim ex-gratia payments, and the reasons for claiming or not claiming. We find that even though wildlife is the major cause of crop loss in the region, especially to elephants, the majority of the respondents (53%) did not claim compensation for the losses. The reasons varied from procedural failures to a negative evaluation of the process or the agency involved but the most recurrent reason for not claiming was a deep religious belief in certain communities on the elephant God, “Mahakal.” Our work indicates that the cultural reverence toward the species is enabling the acceptance of losses. We propose that such complex cultural beliefs and local traditions should be considered when designing schemes that aim to garner conservation support toward damage-causing wildlife species.